Odpowiedzi

2009-11-18T12:52:04+01:00
A) W(x)=x³-2x²-2x+4
łączymy 1 z 2 i 3 z 4
czyli: w(x)=x²(x-2)-2(x-2)
w(X)=(x-2)(x²-2)
w(x)=(x-2)(x-√2)(x+√2)
B) metode dzielenia musisz poznać z książki ja podam ci gotowy wynik, żebyś sobie sprawdził:
x²-2x+20 reszta:64
Najlepsza Odpowiedź!
2009-11-18T12:56:18+01:00
W[x]=x³-2x²-2x+4
W(x)=x²(x-2)-2(x-2)=(x²-2)(x-2)=(x-√2)(x+√2)(x-2)

(x³-6x²+12x-16):(x-4)=x²-2x+4
-x³+4x²
_______
-2x²+12x
+2x²-8x
_________
4x-16
-4x+16
_______
= =
(x³-6x²+12x-16):(x-4)=x²-2x+4
2009-11-18T14:33:46+01:00
W(x)=X³-2x²-2x+4=(x³-2x²)-(2x-4)=x²(x-2)-2(x-2)=
=(x-2)(x²-2)=(x-2)(x-√2)(x+√2)

[x³-6x²+12x-16]:(x-4)=[(x³-6x²)+(12x-16)]:(x-4)